1979
DOI: 10.1093/ajcn/32.5.1159
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the quality of breast milk during 23 months of lactation in a rural community of the Ivory Coast

Abstract: Milk samples from 33 women from a rural area of the Ivory Coast were analyzed once a month. In two longitudinal studies covering 23 months of breast feeding, analyses of lipid components and protein were performed. The compositions remained virtually constant over 23 months of lactation except for a decrease of protein concentration during the first 6 months, a rising trend of myristic acid (14:0) and a falling trend of oleic acid (18:1). Infants were growing well on breast milk with nothing else for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
35
3
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 27 publications
12
35
3
1
Order By: Relevance
“…When the present results are compared with those of a previous study (1), protein and lactose concentrations in milk are found to be similar. Total lipid, phospholipid, triglyceride, cholesterol and therefore calorie content was lower in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…When the present results are compared with those of a previous study (1), protein and lactose concentrations in milk are found to be similar. Total lipid, phospholipid, triglyceride, cholesterol and therefore calorie content was lower in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Lipid phosphorus was determined by the method of Morrison (17). Fatty acid composition of total lipids: Transmethylation and gas chromatography were performed as previously described (1). Ashes, calcium, magnesium, copper, zinc and manganese: Aliquots of lyophilised food samples were incinerated in quartz crucibles at 55°C overnight after carbonisation on a mushroomshaped burner.…”
Section: Food Compositionmentioning
confidence: 99%
“…Prentice et al (1981 b) reported decreasing fat concentration from the first to the fourth trimester of lactation. The observation that fat content of breast-milk decreases with increasing parity (Lauber & Reinhardt, 1979;Prentice et al 1981 b) was not obtained in our study, possibly because the range in parity in this study was very small. Other variables relating to the feeding patterns of the infants, such as milk intake and frequency of suckling, did not predict mean fat concentration as well as the age of the infant, either singly or in combination with other variables.…”
Section: Variation In Fat Concentration Between Mothers and Between Bcontrasting
confidence: 70%
“…The values reported in different studies may be due in part to differences in sampling procedures as well as stage of lactation. Iron content of human milk is highest in early transitional milk (0.97 mg/l) (Lauber and Reinhardt, 1979) but decrease steadily during lactation, reaching a level of approximately 0.35 mg/l at 1 month of lactation to 0.20 mg/l at 6 months (Lemons et al, 1982;Lonnerdal, 1984). The diurnal variation in iron content of breastmilk tend to parallel those reported for fat content with significantly lower mean values in the early morning feeding compared to late evening feeding (Hall, 1979;Fransson and Lonnerdal, 1980).…”
Section: Discussionmentioning
confidence: 99%